2017
DOI: 10.1038/s41467-017-01763-2
|View full text |Cite
|
Sign up to set email alerts
|

Widespread theta synchrony and high-frequency desynchronization underlies enhanced cognition

Abstract: The idea that synchronous neural activity underlies cognition has driven an extensive body of research in human and animal neuroscience. Yet, insufficient data on intracranial electrical connectivity has precluded a direct test of this hypothesis in a whole-brain setting. Through the lens of memory encoding and retrieval processes, we construct whole-brain connectivity maps of fast gamma (30–100 Hz) and slow theta (3–8 Hz) spectral neural activity, based on data from 294 neurosurgical patients fitted with indw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
158
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(185 citation statements)
references
References 59 publications
(73 reference statements)
26
158
1
Order By: Relevance
“…Solomon et al, examined high gamma during verbal-memory and observed both synchronous and asynchronous activity. They found that regions in frontal, temporal, and medial temporal lobe cortex asynchronous with other regions, displayed a high level of connection strength, implying a high level of centrality or hubness within the memory network, a finding broadly consistent with the current results (Solomon EA, et al, 2017). We show that through repetitive processes of memory encoding, gamma frequency activity can establish synchrony to the point that even slow-moving resting-state BOLD fluctuations reflect their network impact.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Solomon et al, examined high gamma during verbal-memory and observed both synchronous and asynchronous activity. They found that regions in frontal, temporal, and medial temporal lobe cortex asynchronous with other regions, displayed a high level of connection strength, implying a high level of centrality or hubness within the memory network, a finding broadly consistent with the current results (Solomon EA, et al, 2017). We show that through repetitive processes of memory encoding, gamma frequency activity can establish synchrony to the point that even slow-moving resting-state BOLD fluctuations reflect their network impact.…”
Section: Discussionsupporting
confidence: 90%
“…Kucewicz and colleagues demonstrated that memory related broadband gamma activity centroids were in the range of 30-100Hz (Kucewicz MT, et al, 2017). Two recent studies on human memory network analysis with a pooled cohort of patients similar to that included in this study, have shown that successful memory encoding is associated with asynchronous organization of the memory network in gamma activity less than 100Hz and synchronous theta activity, with widespread high gamma activity considered to be the hallmark of memory encoding (Solomon EA, et al, 2017;Solomon EA, et al, 2019). In this project, we were interested in investigating the intrinsic BOLD correlations of a high frequency network already known to play a major role in human memory, all toward determining if such networks possess distinctive whole-brain organization properties.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations